Gene expression shapes the patterns of parallel evolution of herbicide resistance in the agricultural weed Monochoria vaginalis. Issue 2 (6th August 2021) - Tanigaki, Shinji; Uchino, Akira; Okawa, Shigenori; Miura, Chikako; Hamamura, Kenshiro; Matsuo, Mitsuhiro; Yoshino, Namiko; Ueno, Naoya; Toyama, Yusuke; Fukumi, Naoya; Kijima, Eiji; Masuda, Taro; et al.
Summary: The evolution of herbicide resistance in weeds is an example of parallel evolution, through which genes encoding herbicide target proteins are repeatedly represented as evolutionary targets. The number of herbicide target‐site genes differs among species, and little is known regarding the effects of duplicate gene copies on the evolution of herbicide resistance. We investigated the evolution of herbicide resistance in Monochoria vaginalis, which carries five copies of sulfonylurea target‐site acetolactate synthase ( ALS ) genes. Suspected resistant populations collected across Japan were investigated for herbicide sensitivity and ALS gene sequences, followed by functional characterization and ALS gene expression analysis. We identified over 60 resistant populations, all of which carried resistance‐conferring amino acid substitutions exclusively in MvALS1 or MvALS3 . All MvALS4 alleles carried a loss‐of‐function mutation. Although the enzymatic properties of ALS encoded by these genes were not markedly different, the expression of MvALS1 and MvALS3 was prominently higher among all ALS genes. The higher expression of MvALS1 and MvALS3 is the driving force of the biased representation of genes during the evolution of herbicide resistance in M . vaginalis . Our findings highlight that gene expression is a key factor in creating evolutionary hotspots.